Sistem Pendukung Keputusan Pemilihan SSD Laptop Berbasis AHP dan TOPSIS - I Gede Parama Sathiyam Yuda Yana; I Gede Arta Wibawa; Putu Praba Santika (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
A decision support system (DSS) is needed to help lay users choose a solid state drive (SSD) that suits their needs and is compatible with their laptops. This study designs and builds a web-based DSS using the Analytical Hierarchy Process (AHP) method for criteria weighting and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method for ranking SSD alternatives. Laptop and SSD data are used to perform matching based on interface compatibility and form factor. The main criteria used include price, capacity, read/write speed, and performance category. This system also provides a criteria comparison feature based on user preferences and presents the best SSD recommendations based on the final TOPSIS score. The test results show that the AHP + TOPSIS method is able to provide more rational and transparent recommendations compared to the manual weighting method.